2005
DOI: 10.1016/j.jacc.2005.05.073
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Etiologic Diagnosis of Cardiac Amyloidosis Using 99m Tc-3,3-Diphosphono-1,2-Propanodicarboxylic Acid Scintigraphy

Abstract: Etiology is a third major cause--in addition to type of organ-involved (soft-tissue/heart) and tracer type--of scintigraphic variability in cardiac amyloidosis. This is a highly relevant consideration for future studies. We conclude that 99mTc-DPD scintigraphy is a useful step in the workup of the differential diagnosis of TTR versus AL etiology in patients with documented cardiac amyloidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
526
1
46

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 777 publications
(578 citation statements)
references
References 30 publications
5
526
1
46
Order By: Relevance
“…Different phosphate derivatives (PYP, MDP, DPD) labelled with 99m Tc seem valuable for detecting cardiac involvement of amyloidosis, but a certain amount of amyloid is necessary. There seems to be no role for this approach in the early detection of cardiac amyloidosis, but it may play a role in the differential diagnosis of ATTR versus AL aetiology in patients with documented cardiac amyloidosis [58]. There is only a limited role for 67 Ga for detection amyloid depositions in the heart with no advantages compared to other tracers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different phosphate derivatives (PYP, MDP, DPD) labelled with 99m Tc seem valuable for detecting cardiac involvement of amyloidosis, but a certain amount of amyloid is necessary. There seems to be no role for this approach in the early detection of cardiac amyloidosis, but it may play a role in the differential diagnosis of ATTR versus AL aetiology in patients with documented cardiac amyloidosis [58]. There is only a limited role for 67 Ga for detection amyloid depositions in the heart with no advantages compared to other tracers.…”
Section: Discussionmentioning
confidence: 99%
“…These patients showed no MDP myocardial uptake. The authors concluded that 99m Tc-DPD scanning is a useful step in the work-up for the differential diagnosis of ATTR versus AL aetiology in patients with documented cardiac amyloidosis [58].…”
Section: Amyloid Deposits 99m Tc-aprotininmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The authors of the current study performed a retrospective analysis in 75 patients with suspected ATTR cardiac amyloidosis who underwent planar Tc99 m PYP cardiac imaging, 48 of whom were reported to have ATTR, 12 with endomyocardial biopsy-proven disease. Myocardial Tc99 m PYP uptake was evaluated on planar images using the established semiquantitative score 5 and the quantitative H/CL chest ratio, 6 although the authors used a semiquantitative score threshold of C1, not C2, for detecting ATTR, in part because they used a 3 hour, not 1 hour, imaging time (see below). They found that both the Tc99m PYP semiquantitative score and H/CL ratio were associated with mortality with HRs of 1.49 (95% CI 1.08-2.08, P = 0.016) and 5.19 (95% CI 1.46-18.4, P = 0.0111), respectively, and with death or heart failure hospitalization with HRs of 1.49 (95% CI 1.17-1.90) and 3.15 (95% CI 1.21-8.23), respectively.…”
mentioning
confidence: 99%
“…In 2005, the Bologna group published data from 25 patients with amyloidosis (17 of whom had TTR-related amyloidosis) suggesting the bone-scanning agent 99m Tc-3,3-diphosphono-1,2-propanodicarboxylic acid (DPD) was preferentially taken up by the heart in patients with TTR amyloidosis, whereas it showed no uptake in AL amyloidosis or in controls without the disease [9]. This appeared to be isotope specific, as 99m Tc-methylene diphosphonate (MDP) showed no uptake in 11 patients who showed distinct myocardial uptake with 99m Tc-DPD.…”
mentioning
confidence: 99%